Event power how global events manage and manipulate - Rojek, Chris (London SAGE, 2013)
Argues that events are essential elements in corporate-state partnerships of 'invisible government' that have revived the romance of charity so to form illusory communities, while cloaking power imbalances and social inequalities.... [an] account of communication power, social ordering and control. -- Page [4] of cover.
Preface: the goodwill newsletter -- What is event management? -- What are the main types of event? -- Why is 'moral regulation' relevant? -- How is event cognition formulated? -- How are global events organised? -- What do cyclical events do? -- Why are we drawn to events? -- What is event consciousness? -- What do single-issue events do? -- Why are events so emotional? -- What is event appropriation? -- Does event management have a future?
Includes bibliographical references and index.
Keywords: Special events -- Management; Special events -- Political aspects; Power (Social sciences); Social control